Quasi-Floating Gate Based High Precision Current Mirror - D. Rajesh,; N. Raj,; P. John Paul, (International Journal of Psychosocial Rehabilitation, 2020)
Current mirror (CM) is a basic building block of several mixed signal circuits such as analog to digital converter, filter etc. The performance metrics of current mirror are its current transfer error ratio, input and output resistances, low input and output compliance voltages and bandwidth response. Out of these metric the current transfer error ratio is more significant parameter as it defines the accuracy of current copying capability in its dynamic range. Various topologies have been proposed with minimum current transfer error ratio. Such errors are greatly affected by the device mismatch governing of its construction parameters. The paper is targeted to achieve minimum current transfer error ratio at sub-volt supply. The proposed circuit uses a feedback loop from input to output and vice versa which enables it to compensate the error responsible of current mismatch. The design is simulated on 180nm node with the help of HSpice simulator